(untitled) (La Rivada, 2023)
This research focuses on the study of ritual cardiectomy among ancient Mayas, in order to understand the symbolic reasons within the Mesoamerican cosmovision that underlie this peculiar religious phenomenon and thus redefine the sacrificial act.